Menilik Aturan Rapid Test di Tengah Adaptasi Kebiasaan Baru (Studi Kasus Kota Makassar) - Ririn Aswandi; Zulistiani Nur Marwah Puteri Madjid; Aqila (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2020)
Abstract In Indonesia, the spread of Covid-19 has spread throughout all existing provinces. Makassar, the capital city of South Sulawesi Province, is currently the main epicenter of thetransmission Covid-19. Makassar City ranks the second district / city with the highest incidence rate or incident rate ofcases Covid-19 in Indonesia. One of the efforts of the Makassar City government in suppressing the spread of Covid-19 is by issuing a regulation requiring its citizens to have afree Covid -19certificate using themethod Rapid Test. However, this rule has exceptions for certain people, which should be no exception because there is no guarantee that the person is free from Covid-19. Because of seeing these problems, the author raises the title